2016
DOI: 10.1038/srep32164
|View full text |Cite
|
Sign up to set email alerts
|

A new (Ba, Ca) (Ti, Zr)O3 based multiferroic composite with large magnetoelectric effect

Abstract: The lead-free ferroelectric 0.5Ba(Zr0.2Ti0.8)O3 − 0.5(Ba0.7Ca0.3)TiO3 (BCZT) is a promising component for multifunctional multiferroics due to its excellent room temperature piezoelectric properties. Having a composition close to the polymorphic phase boundary between the orthorhombic and tetragonal phases, it deserves a case study for analysis of its potential for modern electronics applications. To obtain magnetoelectric coupling, the piezoelectric phase needs to be combined with a suitable magnetostrictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Magnetic metallic alloys or spinel oxides are used for the former component, while ferroelectric polymers or perovskite phases are preferred for the latter one. 2,[4][5][6][7][8] Interest in cofired ceramic composites has grown due to their low cost, easy manufacturing, possibility of co-sintering the magnetostrictive and piezoelectric oxide phases, and high electrical resistivity when compared to metallic alloys as Metglas or Terfenol-D. [9][10][11][12][13][14] Among magnetostrictive phases, CoF e 2 O 4 (CFO) stands out because of its very high magnetostriction (λ). 15 However, studies in ME composites formed by CFO-based compositions mostly resulted in ME coefficients lower than those using N iF e 2 O 4 -based magnetostrictive phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic metallic alloys or spinel oxides are used for the former component, while ferroelectric polymers or perovskite phases are preferred for the latter one. 2,[4][5][6][7][8] Interest in cofired ceramic composites has grown due to their low cost, easy manufacturing, possibility of co-sintering the magnetostrictive and piezoelectric oxide phases, and high electrical resistivity when compared to metallic alloys as Metglas or Terfenol-D. [9][10][11][12][13][14] Among magnetostrictive phases, CoF e 2 O 4 (CFO) stands out because of its very high magnetostriction (λ). 15 However, studies in ME composites formed by CFO-based compositions mostly resulted in ME coefficients lower than those using N iF e 2 O 4 -based magnetostrictive phases.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, studies in ME composites formed by CFO-based compositions mostly resulted in ME coefficients lower than those using N iF e 2 O 4 -based magnetostrictive phases. 9,13,[16][17][18] This is so because the magnetoelectric coupling in composites results from changes of polarization in the piezoelectric phase caused by the dynamical mechanical deformation of the magnetostrictive one under a varying magnetic field. Thus, the relevant characteristic to obtain high ME coupling is a large strain sensitivity dλ dH (or effective piezomagnetic coefficient), and CFO shows low piezomagnetic coefficient because its high magneto-crystalline anisotropy and coercive field.…”
Section: Introductionmentioning
confidence: 99%
“…They also found ε′(f) , frequency dependence of permittivity and found that the ferrite phase partly affected the dielectric response of the composite. They considered BCZT85-CFO15 composite as the best choice for future lead-free materials with higher magnetoelectric properties [126]. Sagar Mane et al prepared multiferroic nanocomposites of x[CoNiFe 2 O 4 ]-(1_x)[0.5(BCT-BZT], x = 0.1, 0.2, 0.3, 0.4, and studied the ε r and tanδ and loss factor as a function of frequency and temperature of the composites.…”
Section: Bczt Thin Films For Enhancement Of Dielectric Propertiesmentioning
confidence: 99%
“…Several bulk magneto-electric composites with ferrites as the magnetostrictive component and either Pb-based or non-Pb-based oxides as piezo-electric component have been investigated to determine the coupling constant as a function of both the contents of the two components as well as processing parameters 814 . Some of the most recent results on bulk composites which are Pb-free are summarized in Table 1 1525 .…”
Section: Introductionmentioning
confidence: 99%